Development of Ips Learning Module Based on Islamic Integration and Science In Grade VII Students SMP Muhammadiyah Enrekang - Darwis, Tri Wijaya; Ibrahim, Muhammad; Suparman, Suparman; Samsul, Putriyani (Journal of Islam and Science, 2021)
The IPS module development based on Islamic integration and science in SMP Muhammadiyah Enrekang based on: First, no SCIENCE teaching materials have the concept of Islamic integration and science. Second, no teaching material guides students to obtain IPS' idea confidence in Allah SWT. Third, the results of studying IPS are some students who have not achieved KKM scores. The purpose of this development are to: (1) design the of Islamic-based IPS modules and human materials science, place and environment in grade VII students of SMP Muhammadiyah Enrekang, (2) explain the effectiveness Islamic-based IPS modules to improve learning outcomes. This research used a Research and Development approach with ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development models. An explanation of the module's level of interest was used in the questionnaire tested in the experiment class. Meanwhile, the influence of modules on improving students' learning outcomes uses pre-test post-test control design groups. The development results showed that: (1) specifications of IPS modules based on Islamic integration and science in the form of print media. This module developed using evidence sourced from the Qur'an. The learning results intended to achieve 2013 curriculum and as a means for students to increase their confidence in Allah SWT through integration with the evidence of the Qur'an; (2) the effectiveness and convenience of IPS module based on Islamic integration and science showed that this module has a high level of feasibility, effectiveness, and interest. 84% level material validation results evidence this, 71% level learning expert validation, 95% level language validation, 90% learning expert validation. The results of field tests on grade VII students of SMP Muhammadiyah Enrekang showed a high level of effectiveness through the works of independent sample t-test obtained t count=6.41and t tabel=2.0322. Because of the t count > table, Ho is rejected, and Ha is accepted